Роль евреев-иностранцев в социально-экономической и культурной жизни Херсонской губернии в конце XVIII – первой половине XIX вв. - Прокоп, Ю.В. (Історичний архів. Наукові студії, 2014)
На основе анализа архивных документов и систематизации имеющихся в
литературе данных выполнено исследование роли евреев-иностранцев в социально-
экономической и культурной жизни Херсонской губернии конца XVIII – первой половины
XIX в. Показано, что евреи-иностранцы внесли значительный вклад в банковское дело,
торговлю и образование, участвовали в подрядах для Черноморского флота и
строительства городских и портовых сооружений. На основі аналізу архівних документів та систематизації наявних в літературі
даних виконано дослідження ролі євреїв-іноземців у соціально-економічному й
культурному житті Херсонської губернії кінця XVIII – першої половини XIX ст. Показано,
що євреї-іноземці зробили значний внесок у банківську справу, торгівлю й освіту, брали
участь у підрядах для Чорноморського флоту й будівництва міських і портових споруд. Based on the analysis of archival documents and ordering data available in literature, the
role of foreign Jews in social-economic life of Kherson province in the end of XVIII – early
XIX century has been investigated.
Rapidly growing cities of Novorossia had an urgent need for specialists of different types and
suppliers, providing construction, trade and normal living conditions for people. Because of that,
among the foreign Jews in the Kherson province were numerous artisans and small traders.
Also there were many merchants. They eager to participate in all kinds of supplies for the Black
Sea Navy, in particular, supplied wood and food. In addition, they participated in contracts for
the construction of various objects.
In the beginning of the XIX century, Jews did not play a prominent role in Odessa trade, and
all leading positions were occupied by the Greeks. But already in 1817 six Jewish merchants
including 4 foreigners are recorded among the traders in the port of Odessa, and later their
number was increasing.
Most of the foreign Jewish merchants in Odessa engaged in trade of fabric and food. Natives
of Galicia occupied leading positions, acting as intermediaries, factors, and agents in the grain
trade. Especially valued among them were bankers.
Leaders in the transit trade in the route Odessa – Brody in the first third of the XIX century
were Jewish merchants from Brody, who for greater efficiency have moved their offices to
Odessa.
Foreign Jews were actively involved in local government.
Enlightened Odessa Jews, among whom more than half were Austrian immigrants, created a
Jewish school in Odessa, in which special attention was paid to training of commerce and
foreign languages. This school was the first institution of its kind in the Russian Empire. Over
time, foreign Jews created other schools in Odessa, as well as in the agricultural colonies of
Kherson province.
Authorities of Novorossia greatly appreciated Jewish foreigners, noting their contribution to
banking, education and charity, as well as the work of Jewish craftsmen. By 1858, three
Austrian Jews were awarded the title of honorary citizens of Odessa.